Characterization of cape gooseberry (Physalis peruviana L.) fruits from plants irrigated with different regimens and calcium doses - Álvarez-Herrera, Javier Giovanni; Vélez, Javier Enrique; Jaime-Guerrero, Marilcen (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Cape gooseberry fruits have positioned in the world market due to their excellent nutritional characteristics, because they are an ideal food that contributes to raising the defenses of the human body and helps it to face diseases such as COVID-19, they are also a natural source of antioxidants and anticancer agents. In order to avoid the physiopathy of cracking in cape gooseberry fruits, these were characterized at harvest time, coming from greenhouse plants irrigated with different applications of water levels and irrigation frequencies, as well as different calcium doses, in a design of randomized complete blocks with 12 treatments. The blocks were the irrigation frequencies (4, 9 and 14 days), while the treatments were the combination of four irrigation coefficients (0.7, 0.9, 1.1 and 1.3 of the evaporation of the tank class A) and three doses of calcium (0, 50 and 100 kg ha-1). The plants were sown in 20 L pots with peat moss substrate.  Fruits were harvested at the color stage 5 and 6 of the calyx, from 19 weeks after transplanting. The different water levels and irrigation frequencies did not significantly affect the firmness of the cape gooseberry fruits, but there was a strong tendency that cracked gooseberry fruits are less firm than healthy fruits. As the irrigation coefficient increased, the total soluble solids (TSS) increased while the total titratable acids (TTA) decreased. Irrigation frequency of 14 days generated fruits with higher TSS and pH values. The calcium doses did not affect the calcium concentration in the fruits or the TSS, TTA and pH values. Therefore, it can be concluded that incremented irrigation coefficients (up to 1.3) increase the quality of cape gooseberry fruits.